DIAGNOSIS KOMUNITAS STATUS KESEHATAN MASYARAKAT - Rokhmayanti Rokhmayanti; Nawwara Putri (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Community diagnosis is an activity to determine the existence of a problem by collecting data in the community. The importance of a community diagnosis because it can identify problems that are broad and cover various aspects of the community. The emergence of health problems is not only caused by individual negligence, but can also be caused by public ignorance as a result of lack of correct information about a disease. The purpose of this study was to obtain an overview of the health problems that exist in RT 11/RW 04 Rejowinangun Village, Kota Gede, Yogyakarta, determine problem priorities and obtain appropriate alternative solutions to overcome the priority problems that have been determined. The method in this activity uses quantitative descriptive analysis with door to door interviews using a community diagnosis questionnaire which is then intervened by counseling and providing health promotion media in the form of posters, pamphlets, hand sanitizers. The result of these activities is that knowledge from the community increases and participants actively ask questions and are enthusiastic in getting the material that has been given. Conclusion: community diagnosis obtained by using a priority scale of problems, namely hypertension and diabetes mellitus. Keywords: Diagnosis, Diabetes Melitus, Hipertensi, Penyuluhan